Directional Interactions of α‐Particles with FOX‐7. A DFT Study. Issue 2 (21st October 2014) - Türker, Lemi
Abstract FOX‐7 is exposed to the effects of α‐particles from selected directions of approach. Various energies and properties of these composite FOX‐7 systems (FOX‐7+α‐particle) are obtained. The effect of α‐particles on FOX‐7 is drastic. The CC double bond turns into a single bond and one of the CNO2 bonds highly elongates. The approach from the side of amino groups results more stable composite system compared to the approach from the side of nitro groups.